2023
DOI: 10.1136/gutjnl-2020-320633
|View full text |Cite
|
Sign up to set email alerts
|

Understanding neuroimmune interactions in disorders of gut–brain interaction: from functional to immune-mediated disorders

Abstract: Functional gastrointestinal disorders—recently renamed into disorders of gut–brain interaction—such as irritable bowel syndrome and functional dyspepsia are highly prevalent conditions with bothersome abdominal symptoms in the absence of structural abnormalities. While traditionally considered as motility disorders or even psychosomatic conditions, our understanding of the pathophysiology has evolved significantly over the last two decades. Initial observations of subtle mucosal infiltration with immune cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 168 publications
(351 reference statements)
0
11
0
Order By: Relevance
“…evidence is largely lacking (23,24). Moreover, the results of duodenal eosinophil counts are highly variable across studies and the largest study to date in 178 patients failed to confirm increased duodenal eosinophil counts even if this study could be criticized for selecting mainly older, male patients based on the outdated Rome II criteria (25).…”
Section: Traditional Gastric Pathophysiologymentioning
confidence: 96%
“…evidence is largely lacking (23,24). Moreover, the results of duodenal eosinophil counts are highly variable across studies and the largest study to date in 178 patients failed to confirm increased duodenal eosinophil counts even if this study could be criticized for selecting mainly older, male patients based on the outdated Rome II criteria (25).…”
Section: Traditional Gastric Pathophysiologymentioning
confidence: 96%
“…Disorders of gut-brain interaction including IBS. DGBI, many of which previously fell under the umbrella of functional GI disorders (Vanuytsel et al, 2023), are experienced by more than 40% of people worldwide (Asnicar et al, 2021). They are characterised by GI symptoms which may present as any combination of motility disturbances, visceral hypersensitivity, altered mucosal and immune function, gut microbiota and/or central nervous system processing (Schmulson & Drossman, 2017).…”
Section: Clinical Implications For Neurogastroenterology and Beyondmentioning
confidence: 99%
“…The pathophysiology of DBGI is not completely understood. However, repeated studies have shown the importance of neuroimmune function and its interaction with luminal microbiota and subsequent impacts on visceral sensitivity and motility 10 . This complex interplay is modulated by psychological state, personality type, and previous life events.…”
Section: Introductionmentioning
confidence: 99%
“…However, repeated studies have shown the importance of neuroimmune function and its interaction with luminal microbiota and subsequent impacts on visceral sensitivity and motility. 10 This complex interplay is modulated by psychological state, personality type, and previous life events. Psychological contributors may be a predisposing, triggering, or perpetuating element, or considered co‐morbid pathology with shared risk factors.…”
Section: Introductionmentioning
confidence: 99%